GAMBARAN KEPATUHAN BEROBAT PASIEN HUMAN IMMUNE DEFICIENCY VIRUS (HIV) DI WILAYAH SEMPAJA SAMARINDA - Yudia, Riries Choiru Pramulia; Wandik, Irma Novalin; Saputra, Shafa Dimas; Siregar, Monica Febriari; Briliant, Oldesta Zakly; Syammarhan, Tiara Ramadhani (Jurnal Kedokteran Mulawarman, 2025)
Human immunedeficiency virus (HIV) is a virus that infects white blood cells and causes a decrease in human immunity. The high number of HIV infections in Indonesia and the low number of patients taking ARVs so this research aims to determine the factors that influence the picture of treatment compliance in HIV patients.Method: This research used descriptive method, and obtained 43 research samples. Then the data is presented in table form. The variables of this study are social support, level of knowledge about antiretroviral therapy (ART), satisfaction with health facilities, and the level of treatment compliance.Results: Univariate analysis found that poor social support (37.2%), the knowledge about ART was good at (83.7), satisfaction with health facilities was very satisfied (95.3%) and the level of compliance was included in the category of compliance with treatment (76.7%). Keywords: HIV, ARV, Social Support, Knowledge, Satisfaction, Compliance